Cybersecurity Challenges in Educational Technology: Protecting Student Data in Digital Learning Platforms - Rafiullah Amin; Jamil Khan; Shazia Akhtar; Rustiyana Rustiyana (Journal Emerging Technologies in Education, 2025)
Background. The widespread adoption of educational technology has transformed teaching and learning, yet it has simultaneously exposed students to heightened cybersecurity risks due to increased data collection, online interactions, and dependence on digital learning platforms. Purpose. This study aims to analyze the key cybersecurity challenges faced by educational institutions and to evaluate the effectiveness of current protection mechanisms in safeguarding student data.   Method. A mixed-method approach was employed, combining a quantitative assessment of security vulnerabilities across 15 widely used learning platforms with qualitative interviews involving IT administrators, teachers, and cybersecurity specialists. Results. The results reveal significant inconsistencies in data encryption standards, inadequate authentication protocols, and limited cybersecurity awareness among platform users. Findings further indicate that institutional policies often lag behind technological advancements, creating systemic exposure to privacy threats. Conclusion. The study concludes that strengthening student data protection requires an integrated framework that combines technological safeguards, user training, and continuous policy updates. These insights underscore the urgency for educational institutions to adopt proactive cybersecurity governance aligned with emerging digital learning demands.